MODEL KEPEMIMPINAN KEPALA DESA BERBASIS KAPASITAS ADAPTIF DALAM MENINGKATKAN KINERJA PELAYANAN PUBLIK DI ERA DIGITAL - Yunita Fourina Dewi; Susilawati Susilawati (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The disruption era demands digital transformation in village governance, yet it is often hindered by apparatus resistance due to manual work culture and low technological literacy. This study aims to explore an adaptive capacity-based village head leadership model to overcome public service issues in Cikande Village. A qualitative case study method was used through data collection from interviews, observations, and documentation of purposively selected informants, namely the village head, service management apparatus, and residents. The findings offer a novelty that grassroots digitalization requires a "positive coercion" strategy, defined as constructive habituation and supervision mechanisms. This strategy integrates technology-based Key Performance Indicators (KPI) with intensive operational mentoring (coaching). This approach has proven capable of reconstructing the apparatus's adaptive capacity, cutting service duration from 1-2 days to mere hours via the ApelDesa system. In conclusion, village e-government effectiveness requires an adaptive transformational managerial approach. These findings expand the discourse of Social Exchange Theory in local bureaucracy and have the potential to become an alternative managerial prototype to support the sustainability of modern village governance.